From China no. 3 to World no. 1 : the strategic practice of BNBM - Zhu, Yan, (SAGE Business Cases., 2017)
BNBM is a state owned enterprise that manufactures gypsum boards for the construction industry. The case examines how BNBM implemented a quality improvement system and transformed the enterprise from manufacturing 45 million square meters of gypsum boards in 2004 to 2.13 billion in 2016.